An Analysis of Verb Usage in Narrative Texts in 10 Bible Character Stories for Sunday School Children - Sanggam Siahaan; Miranda Kristin Lumban Tungkup; Sarah Priscilla Silitonga; Esra Delima Hutabarat; Rimtahi Bahtra V. Marbun; Dwi Angeli Pardede; Ummi Kalsum Siahaan (The Future of Education Journal, 2024)
This study analyzes verb usage in ten Bible character stories designed for Sunday school children, with a specific focus on how various types of verbs contribute to narrative structure and character portrayal. Utilizing a qualitative research design, the study categorizes verbs into four types: transitive, intransitive, inchoative, and stative (e.g., "be"), and examines their distribution and narrative impact. The analysis reveals that intransitive verbs dominate, accounting for 55% of verb usage, thereby highlighting actions as independent events that emphasize the characters' journeys and experiences. Transitive verbs, which comprise 40% of the total usage, underscore interactions and relationships, reinforcing themes of obedience and purposeful action. The limited presence of inchoative and stative verbs suggests a reduced focus on state changes or existential reflections, thereby steering the narrative towards dynamic portrayals of the characters' faith journeys. Overall, this research provides valuable insights into how verb choices shape the storytelling experience and enhance the educational value of biblical narratives for children.